The perception towards the school based curriculum implementation among English teachers at secondary school in Batam - Nindyan Mumpuni, 1966-; Abdul Rahim Hamdan; Fakulti Pendidikan (2010)
Thesis (Sarjana Pendidikan (Kurikulum dan Pengajaran)) - Universiti Teknologi Malaysia, 2010